Photonic Crystal Cavity With Double Heterostructure in GaN Bulk - Yu-Chieh Cheng; Dong-Po Cai; Chii-Chang Chen; Chia-Hua Chan; Chien-Chieh Lee; Ya-Lun Tsai (IEEE Photonics Journal, 2013)
In this study, the photonic crystal cavity has been designed, fabricated, and characterized in GaN bulk materials with the double heterostructure, which can provide high Q-factor. The cavity is characterized by optical pumping. The resonant mode is observed at the wavelength of 362 nm. The threshold of excitation power is found to be 0.9 mW, corresponding to the power density of 12.7 kW/ cm2 . The Q-factor of the cavity is measured to be as high as 104.